Mitochondrial Dysfunction-Associated Arrhythmogenic Substrates in Diabetes Mellitus - Song, Jiajia; Yang, Ruilin; Yang, Jing; Zhou, Lufang (Frontiers in Physiology, 2018)
There is increasing evidence that diabetic cardiomyopathy increases the risk of cardiac arrhythmias and sudden cardiac death. While the detailed mechanisms remain incompletely understood, the loss of mitochondrial function, which is often observed in the heart of patients with diabetes, has emerged as a key contributor to the arrhythmogenic substrates. In this mini review, the pathophysiology of mitochondrial dysfunction in diabetes mellitus is explored in detail, followed by descriptions of several mechanisms potentially linking mitochondrial dysfunction to arrhythmogenesis in the context of diabetic cardiomyopathy.